If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 = 4x + 17 Reorder the terms: 65 = 17 + 4x Solving 65 = 17 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 65 + -4x = 17 + 4x + -4x Combine like terms: 4x + -4x = 0 65 + -4x = 17 + 0 65 + -4x = 17 Add '-65' to each side of the equation. 65 + -65 + -4x = 17 + -65 Combine like terms: 65 + -65 = 0 0 + -4x = 17 + -65 -4x = 17 + -65 Combine like terms: 17 + -65 = -48 -4x = -48 Divide each side by '-4'. x = 12 Simplifying x = 12
| 16-7d=13d+2 | | 30a^2+52a+16= | | 7n^2-8=6n+2n^2 | | x^2-7+2=0 | | 6xy+8yz-7xz-6xy= | | 3+4[x+5]=27 | | 5+9[x+7]=122 | | -32=23m+13-8m | | 3X^2-25X=-2X^2-9X-12 | | 2x^2-rx=20 | | 6[m-3]+4=28 | | -7-p=-6p+8 | | -1+x=7-7x^2 | | 4x-9=10x-3 | | 8+2[p+1]=30 | | 6v+9+3v=-18+2v+9 | | 3.6t-7.2=34.4+8.8t | | -4(r+7)=-69 | | N+12=-8 | | f(x)=(-5-11)(-5+1) | | -18-3x=-48 | | 8+10+2c=-10-5c | | 5(-t-3)=60 | | -5(r+3)=-64 | | 2.5x-2.8=-31.6+9.7x | | -9-26+x=-46 | | 8-3x=21x-49 | | 4x+6y-26=32 | | 5b^2=60b-175 | | 5[a+3]=3a+31 | | 2x^2+x=x^2-20 | | 2d=a-c |